2021
DOI: 10.1007/s40037-021-00686-5
|View full text |Cite
|
Sign up to set email alerts
|

Theory in quality improvement and patient safety education: A scoping review

Abstract: Introduction Theory plays an important role in education programming and research. However, its use in quality improvement and patient safety education has yet to be fully characterized. The authors undertook a scoping review to examine the use of theory in quality improvement and patient safety education. Methods Eligible articles used theory to inform the design or study of a quality improvement or patient safety curriculum. The authors followed scoping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Secondly related theoretical research [ 61 ] were the another focus of this topic. Merely, existing theoretical studies have provided on y limited insights into this topic [ 62 ], three comprehensive theoretical approaches – critical theory, social cognitive theory, and adaptive expertise theory – could be employed in the future to design effective educational strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly related theoretical research [ 61 ] were the another focus of this topic. Merely, existing theoretical studies have provided on y limited insights into this topic [ 62 ], three comprehensive theoretical approaches – critical theory, social cognitive theory, and adaptive expertise theory – could be employed in the future to design effective educational strategies.…”
Section: Discussionmentioning
confidence: 99%
“…To create systems thinkers with a broad toolbox of systems-related skills, faculty and programs are going to need a spectrum of teaching methodologies that goes beyond online modules and experiential learning via QI projects. New approaches that promote deeper engagement and connection with the material, such as transformational learning, 34 simulation, 35 game-based learning, 36,37 and other innovative techniques 38 that can create more meaningful and realistic learning experiences, will be needed. Additionally, efforts should be made to draw stronger connections between SBP and issues that learners perceive as relevant and meaningful.…”
Section: Evolve the Teaching Methodologymentioning
confidence: 99%
“…A more recent realist-inspired review [27] confined itself to a specific type of QI, namely "QI collaboratives" to investigate contexts, mechanisms and outcomes but still included only five (out of 32) primary studies from LMICs. Still, other reviews have confined themselves to 'training and measurement' [28][29][30] and patient safety education [31,32]. No systematic review was found that synthesized literature from LMICs to inform holistic QI policy and practice specifically in PHC.…”
Section: Introductionmentioning
confidence: 99%